2019
DOI: 10.46660/ojs.v10i2.261
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Noise Pollution and Its Impact on the Hearing Capacity of Workers: A Case Study of Gujranwala City, Pakistan

Abstract: The main purpose of this study was to analyze and evaluate the impacts of industrial noise pollution onhearing of workers in Gujranwala. Noise pollution levels were measured at fifty locations with the help of sound levelmeter, which was placed at a height above 1.2 meters from the ground. Two hundred workers were interviewed throughquestionnaire method. Different statistical tests correlation and chi-square were applied to analyze the noise pollutionlevel in Gujranwala city. Impacts of industrial noise pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The noise assessment, which lasted 12 hours and was done in five separate industries in Khulna city of Bangladesh indicated that the jute and power-generating industries exceeded the 90 dB regulatory limit of CPCB and OSHA (Banik et al, 2018). A noise survey conducted at 50 industrial locations in Gujranwala city (Pakistan) revealed that the noise levels were above the WHO's standard limit (Maqsood et al, 2019). In another 24-hour noise monitoring study in two industrial zones of Pakistan reported noise at 102 dB, which was higher than the permissible limit of 75 dB (Farooqi et al, 2019).…”
Section: Industrial Noise Assessmentmentioning
confidence: 96%
See 2 more Smart Citations
“…The noise assessment, which lasted 12 hours and was done in five separate industries in Khulna city of Bangladesh indicated that the jute and power-generating industries exceeded the 90 dB regulatory limit of CPCB and OSHA (Banik et al, 2018). A noise survey conducted at 50 industrial locations in Gujranwala city (Pakistan) revealed that the noise levels were above the WHO's standard limit (Maqsood et al, 2019). In another 24-hour noise monitoring study in two industrial zones of Pakistan reported noise at 102 dB, which was higher than the permissible limit of 75 dB (Farooqi et al, 2019).…”
Section: Industrial Noise Assessmentmentioning
confidence: 96%
“…By modeling, Maya & Sreedevi (2015) were able to get the effect of noise pollution among people and therefore reduce it. By establishing buffer zones that serve as a tool for proximity analysis, the GIS approach has been utilized to define the degree of noise pollution by Maqsood et al, (2019) while studying the impact industrial noise on the hearing capacity of workers. In an academic environment, a similar contour mapping of Kufa University (Kufa River Campus) was carried out using GIS tools, and the spatial fluctuation of noise level was investigated using the Spline interpolation approach (Hussein & Al-Sulttani, 2021).…”
Section: Noise Geospatial Mappingmentioning
confidence: 99%
See 1 more Smart Citation